Incidence of Some Foodborne Pathogens in Retailed Beef Luncheon and Kofta at El-Gharbia Governorate, Egypt - Elbayoumi, Zakaria H.; Edris, Abo Bakr M.; Taha, Dina S.; Shawish, Reyad R. (Journal of Advanced Veterinary Research, 2023)
This study was conducted to evaluate the microbial aspect of some meat products by performing S. aureus count, detection of S. aureus enterotoxins as well as isolation and identification of some food poisoning bacteria. Therefore, fifty random samples of beef luncheon and kofta (25 of each) were equally collected from different localities in Gharbia governorate, then bacteriologically examined, where values of S. aureus count were 7.61×102± 0.54×102 in beef luncheon, 2.82×103± 0.39×103 (cfu/g) in kofta samples. Meanwhile, in beef luncheon enterotoxin B and enterotoxin (A&D) were detected with a percentage of 4% of each, while in kofta samples enterotoxin A, enterotoxin D, and enterotoxin (A&C) were detected with a percentage of 8%, 4%, and 4%, respectively. Moreover, Salmonellae, E. coli, Klebsiella pneumoniae, and Listeria were detected at 16%, 20%, 20%, and 20% in the examined beef luncheon. while, in kofta samples 24 %, 36%, 28% and 16%, respectively. Meanwhile, E. coli identified as O26 : H11, O44 : H18, O78, O91 : H21, O103 : H2, O111 : H4, O127 : H6, O146 : H21 and O159 with various percentages. Salmonella spp. identified as S. Enteritidis, S. Typhimurium, S. Labadi, S. Infantis, and S. Molade. On the other side, Listeria species serologically identified as L. monocytogenes, L. ivanovii, L. innocuai, and L. welshimeri. Moreover, isolated serotypes of K. pneumonia as K1 and K2 were 16%, and 4% in luncheon samples. While 16% and 12% were in kofta samples. Furthermore, high virulent K. pneumonia (HVKP) and classic K. pneumonia (CKP) were 12% and 8% in luncheon, while were 20% and 8% in kofta samples, respectively. Achieved results in the current study proved that most of the examined meat products were contaminated with E. coli, Salmonella spp., S. aureus, Listeria spp. and K. pneumonia, this considered objectionable, as they render the product of inferior quality and unfit for consumption